Roots Routes: Japan, Jamaica, and the Global Flows of Vintage Reggae Vinyl - John Vilanova (Media Industries)
This article excavates the historical, cultural, and music industrial significance of the buying and selling of Jamaican vinyl records in Japan. It reveals an unexpected connection between alternative distribution flows and the persistence of material music in the digital era. The Japanese market for Jamaican records exposes an under-theorized distribution relationship between two island nations on opposite sides of the globe. The durability of this market—launched by amateurs in the 1980s and nurtured into a productive and ongoing discourse—suggests that the materiality of Jamaican vinyl has particular meanings in Japanese culture and that Japan has played an important role in the preservation of Jamaican vinyl. Research consists of interviews with Japanese reggae fans, record store owners, and artists, conducted at reggae record stores throughout Tokyo, Japan. Studying these connections is important because it reorients our approach to flows of music and requires an engagement with the materiality of music-industrial products despite digital distribution’s growing hegemony.